The reality of patients in hemodialysis before COVID-19 pandemic: La realidad del paciente en hemodiálisis antes de la pandemia COVID-19 - Vásquez Bambaren, Mónica (2021)
In a pilot test carried out in the department of Lambayeque (Peru) about the profile of patients who entered hemodialysis for the first time with grade five chronic kidney disease (CKD 5), evidence was found different from other Latin American. The treatment modality for CKD 5 patients increased through hemodialysis according to the Latin American Registry of Dialysis and Kidney Transplantation from 2000 to 2008. In Peru, 84.75% of patients are registered with this form of treatment still in force in our country and others.